Mitochondrial Genetic Diversity in a Captive Malaysian Giant Turtle (Orlitia borneensis) Population: Implications for Conservation Breeding - Andreas Bandang Hardian; Irhamna Putri Rahmawati; Josephine Vanda Tirtayani; Nathan Rusli; Berta Alviyanto; Randy Kusuma; Adwitiya Irene Kumaralalita; Danuja Widigdaya; Safira Kinanti Pribadi; Tania Salsabila Utari; Fitri Ekasari; Anastasia Cahyakusuma Wahyuningtyas; Rini Widayanti; Herdhanu Jayanto (Bogor Agricultural University, Indonesia, 2026)
Generating genetically sustainable assurance colonies of critically endangered Malaysian giant turtles (Orlitia borneensis) for in situ genetic rescue and population reinforcement initiatives requires intensive exploration of genetic profiles, beyond merely providing reproductive viable individuals. When a pedigree and history report are unavailable, a conservation breeding program requires additional genetic information to justify the individual's relatedness and prevent inbreeding and crossbreeding. We proposed a genetic-distance-based parental candidate determination using sequence analyses of mitochondrial ATP synthase subunits 8 and 6 (ATP86), cytochrome c oxidase subunit 1 (CO1), cytochrome B (CytB), and NADH dehydrogenase subunit 4 (ND4). Our study aimed to explore population structure, haplotypes, presumptive genetic localities, and potential genetic markers to determine individuals as parental stock. Our primers successfully amplified partial sequences of the aforementioned encoding genes. Sequence analyses and median-joining haplotype computation revealed potential geographic localities and haplotypes, indicating the presence of conserved populations of the Malaysian giant turtles in Malaysia and Indonesia. Moreover, there was evidence of the establishment of island-based localities in the Sumatra-Belitung cluster population. Our study suggested that more haplotypes and localities, based on Malaysian giant turtle genetics, need to be considered in the captive breeding program. These genetic diversities are pivotal as options and references for pairing parental stocks, helping to prevent heterosis and the loss of specific genetic traits within the Malaysian giant turtle population.